Global, regional, and national burden of motor neuron diseases 1990–2016: a systematic analysis for the Global Burden of Disease Study 2016. Issue 12 (December 2018) - ,; Logroscino, Giancarlo; Piccininni, Marco; Marin, Benoît; Nichols, Emma; Abd-Allah, Foad; Abdelalim, Ahmed; Alahdab, Fares; Asgedom, Solomon Weldegebreal; Awasthi, Ashish; Chaiah, Yazan; Daryani, Ahmad; et al.
Summary: Background: Understanding how prevalence, incidence, and mortality of motor neuron diseases change over time and by location is crucial for understanding the causes of these disorders and for health-care planning. Our aim was to produce estimates of incidence, prevalence, and disability-adjusted life-years (DALYs) for motor neuron diseases for 195 countries and territories from 1990 to 2016 as part of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2016. Methods: The motor neuron diseases included in this study were amyotrophic lateral sclerosis, spinal muscular atrophy, hereditary spastic paraplegia, primary lateral sclerosis, progressive muscular atrophy, and pseudobulbar palsy. Incidence, prevalence, and DALYs were estimated using a Bayesian meta-regression model. We analysed 14 165 site-years of vital registration cause of death data using the GBD 2016 cause of death ensemble model. The 84 risk factors quantified in GBD 2016 were tested for an association with incidence or death from motor neuron diseases. We also explored the relationship between Socio-demographic Index (SDI; a compound measure of income per capita, education, and fertility) and age-standardised DALYs of motor neuron diseases. Findings: In 2016, globally, 330 918 (95% uncertainty interval [UI] 299 522–367 254) individuals had a motor neuron disease. Motor neuron diseases have caused 926 090 (881 566–961 758) DALYs and 34 325 (33 051–35 364) deaths in 2016. The worldwide all-age prevalence was 4·5 (4·1–5·0) per 100 000 people, with an increase in age-standardised prevalence of 4·5% (3·4–5·7) over the study period. The all-age incidence was 0·78 (95% UI 0·71–0·86) per 100 000 person-years. No risk factor analysed in GBD showed an association with motor neuron disease incidence. The largest age-standardised prevalence was in high SDI regions: high-income North America (16·8, 95% UI 15·8–16·9), Australasia (14·7, 13·5–16·1), and western Europe (12·9, 11·7–14·1). However, the prevalence and incidence were lower than expected based on SDI in high-income Asia Pacific. Interpretation: Motor neuron diseases have low prevalence and incidence, but cause severe disability with a high fatality rate. Incidence of motor neuron diseases has geographical heterogeneity, which is not explained by any risk factors quantified in GBD, suggesting other unmeasured risk factors might have a role. Between 1990 and 2016, the burden of motor neuron diseases has increased substantially. The estimates presented here, as well as future estimates based on data from a greater number of countries, will be important in the planning of services for people with motor neuron diseases worldwide. Funding: Bill & Melinda Gates Foundation.